A systematic review of behavioural smoking cessation interventions for people with severe mental ill health—what works?. (6th November 2021) - Spanakis, Panagiotis; Peckham, Emily; Young, Ben; Heron, Paul; Bailey, Della; Gilbody, Simon
Abstract: Background and Aims: People with severe mental ill health smoke more and suffer greater smoking‐related morbidity and mortality. Little is known about the effectiveness of behavioural interventions for smoking cessation in this group. This review evaluated randomized controlled trial evidence to measure the effectiveness of behavioural smoking cessation interventions (both digital and non‐digital) in people with severe mental ill health. Design: Systematic review and random‐effects meta‐analysis. We searched between inception and January 2020 in Medline, EMBASE, PsycINFO, CINAHL, Health Management Information Consortium and CENTRAL databases. Setting and participants: Randomized controlled trials (RCTs) assessing the effects of behavioural smoking cessation and reduction interventions in adults with severe mental ill health, conducted in any country, in either in‐patient or community settings and published in English. Measurements: The primary outcome was biochemically verified smoking cessation. Smoking reduction and changes in mental health symptoms and body mass index (BMI) were included as secondary outcomes. Narrative data synthesis and meta‐analysis were conducted and the quality of included studies was appraised using the risk of bias 2 (RoB2) tool. Findings: We included 12 individual studies (16 articles) involving 1861 participants. The first meta‐analysis (three studies, 921 participants) demonstrated effectiveness of bespoke face‐to‐face interventions compared with usual care across all time‐points [medium‐term: relative risk (RR) = 2.29, 95% confidence interval (CI) = 1.38–3.81; long‐term: RR = 1.58, 95% CI = 1.09–2.30]. The second (three studies, 275 participants) did not demonstrate any difference in effectiveness of bespoke digital on‐line interventions compared with standard digital on‐line interventions (medium‐term: RR = 0.87, 95% CI = 0.17–4.46). A narrative overview revealed mixed results when comparing bespoke face‐to‐face interventions with other active interventions. The methodological quality of studies was mixed, with the majority having some concerns mainly around risk of selective reporting. Conclusions: Face‐to‐face bespoke smoking cessation interventions for adults with severe mental ill health appear to be effective when compared with treatment as usual, but evidence is equivocal when compared with other active interventions. There is limited evidence comparing bespoke digital interventions with generic interventions, and we found no studies comparing them with usual treatment.